Inovação na produção de cuidado integral: desafios e potências em uma unidade de saúde da família no estado de São Paulo - Alves, Marina de Matteu (Universidade Federal de São Carlos, 2023)
The Family Health Strategy (ESF) is a model for producing care in the Primary Health Care (PHC) of the Unified Health System (SUS) in which a multi-professional team is responsible for meeting the health needs of the assigned community, based on a territorial and community approach with the production of bonds and active social participation. This research seeks to analyze the potential and challenges for innovation in comprehensive health care in a Family Health Unit (USF) in São Carlos-SP. In the light of dialectical historical materialism, we analyzed the object of study from its multiple determinations in a movement of transformation generated by social contradictions, from the reference of the social determination of the health-disease process to the disputes over models of health care in the SUS and the actions of professionals at the base of the production of care. Data collection began with observation of daily life at the USF, recorded in a field diary and then through interviews with a semi-structured script. The professionals from the Family Health team (eSF) took part in the research, providing elements for the theoretical translation of the reality they live and construct. The interview data was analyzed using dialectical hermeneutics. It was found that although health workers recognize the existence of multiple determinants of the health-disease process, overcoming the individualistic and sickening culture, which is hegemonic in the way life is lived in society; the medical-centered logic in the production of care, reinforced by the market view of health; the lack of autonomy and freedom in the organization of work processes; and the lack of funding for public health are collective challenges for the production of comprehensive health care. Potential ways of transforming these conditions, in the micro-political sphere, are actions of social innovation, with soft technologies, which recover the capacity to create living work in the encounter between workers and users, producing a bond and comprehensive reception of health needs; the recovery of community coexistence in spaces for health education, promotion and prevention; the permanent education of professionals and social participation. In addition, changes are needed in the organization of macro-policies in order to achieve the agreed guidelines in defense of life and a quality, public SUS.
Innovation in the production of comprehensive care: challenges and potential in a family health unit in the state of São Paulo
Keywords: Atenção primária em saúde; Trabalho vivo; Cuidado integral; Tecnologias leves; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA